A Novel Reduction Technique in the Bridge Plating in Management of Femoral metaphyseo-Diaphyseal Fractures (Journal of Fatima Jinnah Medical University, 2018)
The objective of this study was to evaluate the result of a new reduction technique for bridge plating of femoral fractures. 43 adult patients with fracture of distal diaphyseo-metaphyseal region of femur, presenting in the Accident and Emergency department of Mayo Hospital, Lahore were operated. Bridge plating was done and the fracture fragments were reduced using a novel reduction technique proposed by the author. Postoperative analysis revealed that 93% of the fractures were reduced in an acceptable position in sagittal, coronal and axial plane. The average operative time was less and the average number of persons taking part in surgery was only 3. The authors concluded that this new reduction technique was as good as the conventional methods of reduction of such fractures with the added benefit of being simple and not involving traction table or distractor.